TSUNAMI HAZARD MITIGATION AND THE NOAA NATIONAL WATER LEVEL OBSERVATION NETWORK - James R. Hubbard; Scott A. Duncan (Science of Tsunami Hazards, 2002)
With the renewed interest in regional Tsunami Warning Systems and the potential tsunami threats throughout the Caribbean and West coast of the United States, the National Ocean Service (NOS), National Water Level Observation Network (NWLON) consisting of 175 primary stations, is well situated to play a role in the National Hazard Mitigation effort. In addition, information regarding local mean sea level trends and GPS derived geodetic datum relationships at numerous coastal locations is readily available for tsunami hazard assessment and mapping applications.Tsunami inundation maps and modeling are just two of the more important products which may be derived from NWLON data. In addition to the seven water level gauges that are hardwired into the West Coast and Alaska Tsunami Warning Center (WClATWC), NOS has a significant number of gauges with real-time satellite telemetry capabilities located along the Pacific Northwest coastline, the Gulf of Mexico and the Caribbean. These gauges, in concert with near shore buoy systems, have the potential for increasing the effectiveness of the existing tsunami warning system.The recent expansion of the Caribbean Sea Level Gauge Network through the NOS regional partnerships with Central American and Caribbean countries have opened an opportunity for a basin-wide tsunami warning network in a region which is ill prepared for a major tsunami event.